Serum level of 25‐hydroxyvitamin D and obesity among early pregnant women. Issue 12 (5th September 2019) - Mahmoud, Sally Z.; Saad, Alfarazdeg A.; Mohieldein, Abdelmarouf H.; Nasr, Abubakr M.; Adam, Ishag
Abstract: Aim: To assess serum 25‐hydroxyvitamin D 25(OH)D level in obese pregnant Sudanese women in early pregnancy. Methods: A match case–control study was conducted in Saad Abualila Hospital (Khartoum, Sudan). The cases were obese (body mass index [BMI] ≥ 30.0 kg/m 2 ) women. Controls were women with normal BMI (18.5–24.9 kg/m 2 ) matched for age, parity and gestational age. The 25(OH)D level was measured using ELISA. Results: There was no significant difference between the two groups in their age, parity or gestational age. There was no significant difference in the median (interquartile) level of the serum (25(OH)D between obese pregnant women and normal weight pregnant women (3.05 [11.100–15.937] ng/ml vs 13.05 [10.950–17.362] ng/ml, P = 0.237). There was no significant correlation between BMI and 25(OH)D level ( r = −0.133, P = 0.149). Conclusion: There was no significant difference in the 25(OH)D level between the obese pregnant women and normal weight pregnant women in this study.